2004
DOI: 10.1101/gr.2264004
|View full text |Cite
|
Sign up to set email alerts
|

The Atlas Genome Assembly System

Abstract: Atlas is a suite of programs developed for assembly of genomes by a "combined approach" that uses DNA sequence reads from both BACs and whole-genome shotgun (WGS) libraries. The BAC clones afford advantages of localized assembly with reduced computational load, and provide a robust method for dealing with repeated sequences. Inclusion of WGS sequences facilitates use of different clone insert sizes and reduces data production costs. A core function of Atlas software is recruitment of WGS sequences into appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 42 publications
0
103
0
2
Order By: Relevance
“…We are tempted to conclude that differences in the assembler were responsible for the higher level of fragmentation in D. pseudoobscura. The Freeze 1 assembly of D. pseudoobscura was done with ATLAS (Havlak et al 2004), while the D. persimilis assembly was done as assisted assembly using an ARACHNE assembly of the D. pseudoobscura genome. The D. persimilis assembly appears to be less fragmented through a more aggressive joining of contigs, which led to mis-joins.…”
Section: Discussionmentioning
confidence: 99%
“…We are tempted to conclude that differences in the assembler were responsible for the higher level of fragmentation in D. pseudoobscura. The Freeze 1 assembly of D. pseudoobscura was done with ATLAS (Havlak et al 2004), while the D. persimilis assembly was done as assisted assembly using an ARACHNE assembly of the D. pseudoobscura genome. The D. persimilis assembly appears to be less fragmented through a more aggressive joining of contigs, which led to mis-joins.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing reactions were performed using BigDye version 3.1 (Applied Biosystems), and analyzed on ABI 3700 sequencing machines. These reads were assembled using the Atlas suite of assembly tools (Havlak et al 2004). The Atlas suite identifies relatively small groups of reads that contain sequence overlap, assembles these groups individually, and uses paired-end information to join the resulting contigs into large scaffolds.…”
Section: Sequencing and Assemblymentioning
confidence: 99%
“…Detection of copy-number losses, however, can be caused by a deletion in the test samples, by a gain in the control sample or by a combination of both. To determine whether some of the apparent deletion regions may be due to sequence duplications in the control sample from strain C67BL/6J rather than bona fide deletion in the test samples, we use an oligomer counting approach 3 (Supplementary Methods online) to analyze the copy-number variations across the genome of the C57BL/6J strain. We found that BAC clones showing loss were more frequently (P o 0.0023, w 2 test) located in regions with higher copy number in strain C57BL/6J, suggesting that the reduced copy number in the test strains may not be caused by real deletion.…”
mentioning
confidence: 99%